2019
DOI: 10.1016/j.pocean.2019.102172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the ecological status of cold-water coral habitats using non-invasive methods: An example from Cassidaigne canyon, northwestern Mediterranean Sea

Abstract: Cold-water coral ecosystems have been identified as vulnerable, but quantitative data on their conservation status is very limited. The Marine Strategy Framework Directive (MSFD) is the tool implemented by the European Union's Integrated Maritime Policy to achieve Good Environmental Status (GES) of marine waters by 2020. In this context, the aim of this study was to evaluate the Ecological Status of benthic habitats in Cassidaigne canyon, focusing in particular on cold-water coral habitats dominated by Madrepo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Such differences result into a high degree of physical and biological variability at both the intra-and inter-canyon level (McClain and Barry, 2010;Wü rtz, 2012), so that understanding factors driving community composition can be very challenging. Recent advances in technology such as Remotely Operated Vehicles (ROVs), swath bathymetry and side-scan sonar have allowed to better understand geomorphological features, processes and biodiversity through a non-invasive procedure based on underwater footage (Fernández-Arcaya et al, 2017;Canals et al, 2019;Chimienti et al, 2019a,b;Fabri et al, 2019). However, knowledge of the benthic communities' species richness, composition, and factors regulating their variability at different spatial scales is still scant.…”
Section: Introductionmentioning
confidence: 99%
“…Such differences result into a high degree of physical and biological variability at both the intra-and inter-canyon level (McClain and Barry, 2010;Wü rtz, 2012), so that understanding factors driving community composition can be very challenging. Recent advances in technology such as Remotely Operated Vehicles (ROVs), swath bathymetry and side-scan sonar have allowed to better understand geomorphological features, processes and biodiversity through a non-invasive procedure based on underwater footage (Fernández-Arcaya et al, 2017;Canals et al, 2019;Chimienti et al, 2019a,b;Fabri et al, 2019). However, knowledge of the benthic communities' species richness, composition, and factors regulating their variability at different spatial scales is still scant.…”
Section: Introductionmentioning
confidence: 99%
“…To date, seven CWC provinces, structured by the colonial scleractinians Madrepora oculata and, subordinately, Desmophyllum pertusum (Lophelia pertusa; Addamo et al, 2016), have been identified in the Mediterranean Sea (Taviani et al, 2017(Taviani et al, , 2019Chimienti et al, 2019). From east to west, the CWC provinces are Bari Canyon (e.g., Freiwald et al, 2009;Angeletti et al, 2014Angeletti et al, , 2020 and Santa Maria di Leuca (Taviani et al, 2005;Vertino et al, 2010) in the Adriatic and Ionian seas, South Malta (Schembri et al, 2007;Freiwald et al, 2009;Knittewis et al, 2019), South Sardinia Nora Canyon (Taviani et al, 2017) in the Tyrrhenian Sea, Cassidaigne (Fabri et al, 2014(Fabri et al, , 2019 and Cap de Creus canyons (Orejas et al, 2009) in the Gulf of Lion, and Alboran Sea (Lo Iacono et al, 2019, with references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Entanglements in marine animal forests and related damage have been recognized as important indicators of stress for benthic communities in both shallow and deep waters (Angiolillo et al, 2015; Bo, Bava, et al, 2014; Bo, Cerrano, et al, 2014; Enrichetti et al, 2019; Galgani, Pham, Claro, & Consoli, 2018; Gori et al, 2017). Fragile, slow‐growing species, such as Callogorgia verticillata or cold‐water carbonate corals, provide useful insight into the resistance and resilience of deep benthic assemblages to mechanical stressors (Bo, Bava, et al, 2014; Bo, Cerrano, et al, 2014; Fabri et al, 2019). The Callogorgia verticillata population of the Ulisse Seamount is ultimately characterized by three distinct groups: (i) a large proportion of healthy juvenile colonies, indicating regular successful recruitment in the area; (ii) an intermediate proportion of medium‐sized adult colonies living on highly exploited, gently sloping, silted hardgrounds and dead coral frameworks, and showing evident traces of mechanical stress (dead, entangled, or broken); and (iii) a residual portion of large adult colonies with a relatively good health status thriving on the rough rocky outcrops of the shallowest part of the summit, which fishermen are likely to try to avoid to reduce gear loss.…”
Section: Discussionmentioning
confidence: 99%